Mapping nationally adopted targets for antimicrobial consumption and stewardship indicators in the human health domain, 25 European Union/European Economic Area countries, 2025 - Liselotte Diaz Högberg; Vera Vlahović-Palčevski; Vivian H Leung (Eurosurveillance, 2026)
BACKGROUND Establishing quantifiable targets for antimicrobial consumption (AMC) and stewardship activities can provide a structured framework for monitoring and evaluating progress in efforts to curb antimicrobial resistance (AMR). AIM We aimed to map the presence and characteristics of national AMC-related targets in the human health domain across European Union (EU)/European Economic Area (EEA) countries, thereby creating an inventory to inform current and future target-setting initiatives. METHODS We performed a survey within the European Surveillance of Antimicrobial Consumption Network (ESAC-Net) to identify national AMC-related targets in force for 2025 or later. RESULTS Based on responses received from 25 EU/EEA countries, we identified a total of 67 nationally adopted AMC-related targets, active for 2025 or beyond, from 16 countries. Targets for population-level AMC indicators were the most frequently reported (73%), followed by patient-level AMC indicators (18%) and structural stewardship indicators (9%). The influential role of the 2023 EU Council Recommendation on AMR and its recommendations for national targets was particularly evident in our findings. CONCLUSION This inventory provides examples of national targets and related implementation and monitoring frameworks used across a range of settings and resource levels. Our findings highlight the importance of robust and sustainable surveillance infrastructure and reporting systems to support the development, implementation, monitoring and evaluation of AMC-related national targets. Such systems are also needed to enable targets that capture prescribing practices and antimicrobial stewardship activities, beyond overall consumption volume metrics alone.